Pengaruh Pelatihan, Pendampingan, dan Pembinaan Pemerintah Kota Melalui Pusat Layanan Usaha Terpadu Koperasi Usaha Mikro Kecil Menengah (PLUT-KUMKM) Terhadap Peningkatan Pendapatan Umkm di Kota Kupang - Desi Rahmiyanti; Deanita Sari (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
UMKM become independent businesses that can create jobs so that UMKM can contribute to the decline in the unemployment rate in an area. Providing government support to improve the quality and quantity of production with the aim of increasing MSME income, provided through support for improving human capital (Human Capital) or improving the quality of business actors. With the holding of Training, Assistance, and Guidance from the Kupang City Government through PLUT-KUMKM, it is hoped that the improvement of the quality of business actors can increase so that it affects the income of UMKM. The data analysis techniques used are multiple linear regression and classical assumption tests. Analysis using the help of the SPSS version 25 program. The results of the simultaneous test showed that the variables of training, mentoring, coaching of the Kupang City Government had a positive effect on the income of UMKM. In terms of training, mentoring, coaching the Kupang City Government through PLUT-KUMKM has a significant effect on the income of UMKM.